Salient and recess development in the Agrio - Aluminé fold and thrust belt. Influence of a pre-Andean foreland obstacle - Yagupsky, Daniel Leonardo (2013)
Curved traces are recurrent features of structural map-view patterns on different fold and thrust belts (FTB) of the world . Although curving FTB frequently reflect pre-deformational thickness of the sedimentary basin fill , other causes are also common. These include interaction of the growing orogenic wedge with foreland obstacles or promontories, and intersection between two non-coaxial (and possibly diachronic) belts, among others . In such cases, a recess is expected to form against the basement high or where non-coaxial belts overlap, and a salient away from it. These map-view curvatures are commonly accompanied by significant morphological, structural and stratigraphic changes. The Agrio and Aluminé fold and thrust belts occur along the Andean foreland region between 37° and 40°30?S. They involve several thousands of meters of a Mesozoic succession accumulated under variable tectonic and sedimentary conditions in the Neuquén basin. Different lines of evidence indicate that both portions of the fold and thrust belt developed in at last two discrete periods of progression of deformation toward the foreland. The first occurred in Late Cretaceous times, and the last one between the Middle Miocene and the Lower Pliocene There is a striking difference in the degree of progress of the deformation towards the east between both belts, delineating a wider northern portion that defines a salient (Chiuhuidos salient), and a narrower southern portion that becomes a recess (Laguna Blanca recess). Significant morphological, stratigraphic, and structural changes occur around 38°30´S, on the transitional area between both segments.